The teaching process of electrocardiography in medical careers - Yanelka Bouza Jiménez; Pedro Miguel Milián Vázquez; María Magdalena López Rodríguez del Rey; Enrique Acosta Figueredo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Foundation: teaching of clinical electrocardiography during doctor´s training in Cuba has been characterized by the insufficient content treatment in the subjects of the curriculum, despite its importance for professional performance. Objective: to propose a curricular strategy for content treatment of clinical electrocardiography in the medical training program. Methods: the research was developed at the Cienfuegos University of Medical Science. The theoretical analysis allowed establishing the requirements for the treatment of electrocardiography as content of the training program. These requirements, together with the diagnosis which confirmed the potential offered by the curriculum of the medical degree to address the content, allowed the design of a curricular strategy oriented towards this objective. Results: the curricular strategy proposes a didactic clinical electrocardiography content sequencing in each year or cycle of the curriculum, modifying the role of the teacher and the student in its teaching-learning process, by granting a special connotation at the curricular level by mainstreaming this content treatment and the teaching tasks that students can solve throughout the career. Expert´s assessment allowed us to confirm the validity of the curricular strategy as its relevance, feasibility, sustainability and transferability were verified. Conclusions: the strategy presented will help to resolve the medical career curriculum insufficiency in terms of electrocardiography content.